The effect of glycerol loading on Olympic distance triathlon performance in hot and humid conditions - Coutts, A.; Reaburn, P.; Holmes, M.; Mummery, W.
The current results suggest that glycerol ingestion conveys a significant increase in total body water content and presents significant ergogenic benefits during ODT (Olympic distance triathlon) in very hot and humid conditions.